Interactive effect of ammonium and nitrate on the nitrogen uptake and biomass production by Chlorella vulgaris in different environmental conditions - R., Taheri; M., Shariati (Penerbit Universiti Kebangsaan Malaysia, 2014)
Microalgae assimilate different types of nitrogen by interacting in different areas. The interactive effect of uptake rate and biomass production of Chlorella vulgaris was investigated under summer and fall environmental conditions. C. vulgaris was cultivated in a media containing 1 mM NH4Cl, 0.5 mM NH4Cl + 0.5 mM KNO3, and 1 mM KNO3 as the nitrogen source.Nitrate and ammonium was more rapidly utilized when both were available. C. vulgaris preferred ammonium to nitrate in the fall condition, but both nitrate and ammonium were completely assimilated in the summer condition. The uptake rate of nitrate and ammonium in the summer condition was significantly higher (p < 0.01) than in the fall condition and the summer/fall ratio for nitrate uptake (290%) was significantly higher (p < 0.01) than for ammonium (120%). In all experiments,biomass production in the summer condition was significantly higher than fall condition (p < 0.01). The highest biomass was during the summer condition (5 g/l (f wt)) from the medium containing NO3-as the nitrogen source. C. vulgaris recorded faster growth in the NO3 - and (NO3- + NH4+) media than in the NH4+ medium. The summer/fall ratio of biomass production was 235%, 300%, and 265% for the media containing NO3 -, NH4+, and (NO3- + NH4 +), respectively.